2020
DOI: 10.1039/d0sc01045f
|View full text |Cite
|
Sign up to set email alerts
|

A bioinspired molybdenum–copper molecular catalyst for CO2 electroreduction

Abstract: A bimetallic Mo–Cu complex inspired by the active site of the carbon monoxide dehydrogenase enzyme mediates the electroreduction of carbon dioxide to formic acid.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…In 2020, Mougel and coworkers synthesized [(bdt)Mo(O)S 2 CuCN] 2− (8) (bdt = benzenedithiolate) as a MoCu-CODH model complex (Scheme 5) [42]. The Mo and Cu were bridged by µ 2 -sulfide ligand as the enzyme active site, and a bdt ligand was used to model the MPT.…”
Section: Mocu-codh Analogsmentioning
confidence: 99%
“…In 2020, Mougel and coworkers synthesized [(bdt)Mo(O)S 2 CuCN] 2− (8) (bdt = benzenedithiolate) as a MoCu-CODH model complex (Scheme 5) [42]. The Mo and Cu were bridged by µ 2 -sulfide ligand as the enzyme active site, and a bdt ligand was used to model the MPT.…”
Section: Mocu-codh Analogsmentioning
confidence: 99%
“…3). [20] Beyond the identification of a new selective catalyst for CO 2 reduction, this study allowed an unknown activation pathway of the bio-inspired active site to be identified. It highlights that such studies also have the potential to provide feedback to the investigation of the enzymatic system via the study of simple models of their active site.…”
Section: Reactant Management At the Macroscalementioning
confidence: 99%
“…5 CO 2 reduction involving multiple electron transfers coupled with proton transfers is less expensive but more complex. In recent years, significant progress has been achieved, 6,7 and many elegant transition metal-based electrocatalysts have been reported, such as Re, 8–10 Ru, 11–13 Fe, 14–16 Co, 17–20 Ni, 21,22 Cu, 23,24 Mn, 25 and Mo 26 complexes.…”
Section: Introductionmentioning
confidence: 99%